Zarządzanie ryzykiem - Ciekanowski, Zbigniew; Wyrębek, Henryk (De Securitate et Defensione. O Bezpieczeństwie i Obronności, 2016)
Risk is a phenomenon associated with any activity aimed at achieving its objectives. This phenomenon arises from the different risks of incurring losses by entrepreneurs and other business entities. Today, an increasing number of situations to take risks. All organizations, regardless of size come into contact with internal and external factors that give rise to uncertainty. The result of this uncertainty is the risk associated with any type of business. It is therefore important to any enterprise undertaken measures to reduce uncertainty and a list of wrong decisions causing a risk of action. This paper is descriptive in which the analysis of the source. The article presents the significance and conditions of enterprise risk management.